The Effect of Utilization of Accounting Information Systems and Quality of Human Resources on the Quality of Financial Reports - Hansen Kant Wee Han; Novera Kristianti Maharani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
The purpose of this study is to determine the influence of Accounting Information System utilization and human resource quality on the quality of financial reports. For the 2018-2020 timeframe, this research will focus on Sahabat Agro Group Ltd, an oil palm plantation company. Primary data were collected using questionnaires with a total of 36 samples. In this study, descriptive statistics, validity and reliability tests, classical assumption tests, and hypothesis testing are used in the analysis. The findings indicate that while the deployment of accounting information systems improves the quality of financial reports, the quality of human resources improves the quality of financial reports. Simultaneous usage of accounting information systems with high-quality human resources, on the other hand, improves the quality of financial reporting.